2018
DOI: 10.1111/josi.12284
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Leadership and the Masculinity Contest Culture: How “Win or Die” Cultures Breed Abusive Leadership

Abstract: Recent years have witnessed an increase in scholarly and practitioner interest in the effects of toxic forms of leadership and “win or die” organizational cultures in which employees seek to maintain their own status at all costs, yet there is little research examining the interaction of this type of leadership style and organizational culture. In this survey study of working adults, we demonstrate an association between perceptions of toxic leadership and “masculinity contest cultures” (Berdahl, Cooper, Glick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 63 publications
8
72
3
1
Order By: Relevance
“…As expected, masculinity contest norms tended to be strongly correlated with other organizational‐level measures (other culture measures and dominance behaviors from coworkers), moderately correlated with measures of individuals’ relationship to work, and weakly correlated with personal outcome measures such as general psychological or physical health. Similar results (with the MCC relating to negative workplace culture and outcomes) have been obtained by Rawski and Workman‐Stark () within a police organization and Matos, O'Neill, and Lei () in a general worker sample (we review unanticipated effects found by Matos et al. in detail below).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As expected, masculinity contest norms tended to be strongly correlated with other organizational‐level measures (other culture measures and dominance behaviors from coworkers), moderately correlated with measures of individuals’ relationship to work, and weakly correlated with personal outcome measures such as general psychological or physical health. Similar results (with the MCC relating to negative workplace culture and outcomes) have been obtained by Rawski and Workman‐Stark () within a police organization and Matos, O'Neill, and Lei () in a general worker sample (we review unanticipated effects found by Matos et al. in detail below).…”
Section: Discussionsupporting
confidence: 84%
“…Although Matos et al. () similarly showed that masculinity contest norms correlate with greater stress, higher turnover intentions, and more work–life conflict, they also found some paradoxical relationships. Specifically, masculinity contest norms correlated (weakly) with greater job engagement and job meaning—constructs we did not assess.…”
Section: Discussionmentioning
confidence: 96%
“…While men gave low ratings to abusive female leaders and women gave low ratings to both male and female abusive leaders, men seemed to tolerate abusive behaviors from a male leader to a somewhat higher extent. It is possible this may be partly explained by cultural notions of masculinity or masculinity contest cultures (Matos et al 2018), prescribing socially dominant and even abusive behavior as acceptable or even desirable among men.…”
Section: Discussionmentioning
confidence: 99%
“…2013), conversely such climates can also become toxic. Toxic forms of leadership include the masculinity dynamics of “win or die” and while toxic leadership is associated with lower work engagement and job meaningfulness, with men who report having a toxic leader, there is a slight increase in work engagement and work meaningfulness (Matos, O'Neill, & Lei, 2018). Toxic leaders can focus on gaining control through rudeness, coercion, arrogance, and inflexibility and rationalize their behavior as necessary to get the job done (Pelletier, 2010; Reed, 2004).…”
Section: Individualism Collectivism Masculinity and Power Distancementioning
confidence: 99%